2019
DOI: 10.1109/access.2019.2896731
|View full text |Cite
|
Sign up to set email alerts
|

Study on Influence of Ultrasonic Vibration on the Ultra-Precision Turning of Ti6Al4V Alloy Based on Simulation and Experiment

Abstract: Titanium alloy is one of the most important metals widely used in many industrial fields due to its special performance, such as high corrosion resistance and specific-strength. In recent years, titanium alloy has a great application prospect in the optical field. However, the pitiful machinability of titanium alloy material brings great difficulty to its ultra-precision cutting. In this paper, we have proposed the method of ultrasonic-assisted ultra-precision turning (UAUT) to improve the cutting performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Thepsonthi [ 17 ] simulated the micro-end milling of titanium alloy using an established 3D finite element model. Hu [ 18 ] used the finite element technique to study the mechanism of chip formation in the ultrasonic assist ultra-precision cutting of titanium alloy. Wu [ 19 ] developed a 3D milling model to simulate the cutting model to investigate the cutting phenomenon of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Thepsonthi [ 17 ] simulated the micro-end milling of titanium alloy using an established 3D finite element model. Hu [ 18 ] used the finite element technique to study the mechanism of chip formation in the ultrasonic assist ultra-precision cutting of titanium alloy. Wu [ 19 ] developed a 3D milling model to simulate the cutting model to investigate the cutting phenomenon of titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al 30,31 studied the effects of the continuous minimum quantity lubrication with ultrasonic vibration in turning of titanium alloy, and the results illustrated that UAT lowered cutting force due to the combined advantages of lubrication and vibration, furthermore the cutting force was decreased with the cutting speed and tool frequency increased. Hu et al 32 researched the influence of ultrasonic vibration on the ultra-precision turning of Ti6Al4V based on simulation and experiment, and it demonstrated that UAT could reduce the cutting force and residual stress compared to CT.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, many methods were presented to reduce the tool wear and improve the cutting quality of titanium alloys in the cutting process. 15–22 Braham et al. 15 used the laser-assisted machining to improve the machinability of titanium alloys by using the thermal softening effect and the investigation showed that the chip formation mechanisms are also changed by increasing the sawteeth frequency when using laser assistance.…”
Section: Introductionmentioning
confidence: 99%